Increasing Heat‐Stress Inequality in a Warming Climate. Issue 2 (4th February 2022) - Alizadeh, Mohammad Reza; Abatzoglou, John T.; Adamowski, Jan F.; Prestemon, Jeffrey P.; Chittoori, Bhaskar; Akbari Asanjan, Ata; Sadegh, Mojtaba
Abstract: Adaptation is key to minimizing heatwaves' societal burden; however, our understanding of adaptation capacity across the socioeconomic spectrum is incomplete. We demonstrate that observed heatwave trends in the past four decades were most pronounced in the lowest‐quartile income region of the world resulting in >40% higher exposure from 2010 to 2019 compared to the highest‐quartile income region. Lower‐income regions have reduced adaptative capacity to warming, which compounds the impacts of higher heatwave exposure. We also show that individual contiguous heatwaves engulfed up to 2.5‐fold larger areas in the recent decade (2010–2019) as compared to the 1980s. Widespread heatwaves can overwhelm the power grid and nullify the electricity dependent adaptation efforts, with significant implications even in regions with higher adaption capacity. Furthermore, we compare projected global heatwave exposure using per‐capita gross domestic product as an indicator of adaptation capacity. Hypothesized rapid adaptation in high‐income regions yields limited changes in heatwave exposure through the 21st century. By contrast, lagged adaptation in the lower‐income region translates to escalating heatwave exposure and increased heat‐stress inequality. The lowest‐quartile income region is expected to experience 1.8‐ to 5‐fold higher heatwave exposure than each higher income region from 2060 to 2069. This inequality escalates by the end of the century, with the lowest‐quartile income region experiencing almost as much heatwave exposure as the three higher income regions combined from 2090 to 2099. Our results highlight the need for global investments in adaptation capabilities of low‐income countries to avoid major climate‐driven human disasters in the 21st century. Plain Language Summary: We show that heatwave exposure has disproportionately increased in the lowest‐income regions globally compared to the highest‐income regions over the past four decades. We also show that emerging heat hazards (e.g., shock heatwaves—the first heatwave of the season—and widespread contiguous extreme heat events) intensified in the past four decades and are expected to increase in the future across the globe, jeopardizing adaptation efforts even in wealthy countries. We use climate projections to evaluate future changes in heat‐stress inequality globally. In doing so, we incorporate the fact that high‐income countries have greater institutional and individual capacity to rapidly adapt to climate change than low‐income countries. Our findings demonstrate continued increases in heatwave exposure inequality because of delays in adaptation capacity in the developing world, compounded by a higher emergence of warming in low‐latitude areas where most of the low‐income countries occur. These results highlight the urgency to scale adaptation efforts in the low‐income regions to minimize heat‐stress inequality. Key Points: Heatwave exposure in the recent decade was >40% higher in the lowest‐quartile income region of the world than the highest‐quartile Rapid adaptation capacity in higher‐income regions can buffer climate change‐driven increases in heatwave exposure Lagged adaptation in the lower‐income regions translates to escalating impacts and increasing heat‐stress inequality